The journal of Biddy Owens : the Negro leagues - Myers, Walter Dean, 1937- (New York : Scholastic, 2001)
Teenager Biddy Owens' 1948 journal about working for the Birmingham Black Barons includes the games and the players, racism the team faces from New Orleans to Chicago, and his family's resistance to his becoming a professional baseball player. Includes a historical note about the evolution of the Negro Leagues
Keywords: Birmingham Black Barons (Baseball team) -- Juvenile fiction; Birmingham Black Barons (Baseball team) -- Fiction; African Americans -- Juvenile fiction; Baseball stories; Negro leagues -- Fiction; African Americans -- Fiction; Segregation -- Fiction; Prejudices -- Fiction; Diaries -- Fiction; Fiction